Measuring complementarity - implications for co-located wave energy (Proceedings of the European Wave and Tidal Energy Conference, 2025)
One of the key problems with integrating renewable energy in the power grid is the inherent variability and uncertainty. One way of mitigating this issue is using complementary energy sources, that when combined reduce variability and increase system reliability or optimize resource utilization. In this paper, various metrics for renewable energy complementarity are reviewed. Definitions, methodologies and interpretations of the metrics are provided.A particular focus is placed on the implications of the metrics for wave energy. The temporal characteristics of wave energy is often similar to that of wind power, with a time delay. Therefore, combining wave energy with wind energy as well as other energy sources offer opportunities for synergetic co-location strategies.The paper acts as a reference map for when to use which complementarity metric, and what the metric means. Our finding underscores the importance of leveraging energy complementarity, and aids to avoid pitfalls in wrongly assessing complementarity.